Chemical variables - lake from Erssjön, Floating platform - Skogaryd Research Catchment (University of Gothenburg, 2024)
Manual grab samples for chemical analysis are taken from the lake on a biweekly basis during ice-free conditions, and on a monthly basis during ice cover conditions. At the central lake sampling location water samples are collected from both epi- and hypolimnion during periods of stratification.
Skogaryd Research Catchment (2024). Chemical variables - lake from Erssjön, Floating platform, 2017-05-15–2019-11-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/8TgYOFsvnD_022cfVt5BtKbL
Keywords: Skogaryd Research Catchment; Lake/Pond; Time instant; Time instant; pH; pH; Electrical conductivity; Electrical conductivity; Water temperature; Water temperature; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrite-N/Nitrate-N; Nitrite-N/Nitrate-N; Sulphate-S; Sulphate-S; Fluorine; Fluorine; Chlorine; Chlorine; Aluminium; Aluminium; Boron; Boron; Calcium; Calcium; Iron; Iron; Potassium; Potassium; Magnesium; Magnesium; Manganese; Manganese; Sodium; Sodium; Phosphorus; Phosphorus; Sulfur; Sulfur; Silicon; Silicon; Zinc; Zinc; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap